In vivo EPR extracellular pH‐metry in tumors using a triphosphonated trityl radical. Issue 6 (1st July 2016) - Marchand, Valérie; Levêque, Philippe; Driesschaert, Benoit; Marchand‐Brynaert, Jacqueline; Gallez, Bernard
Abstract : Purpose: The ability to assess the extracellular pH (pHe) is an important issue in oncology, because extracellular acidification is associated with tumor aggressiveness and resistance to cytotoxic therapies. In this study, a stable triphosphonated triarylmethyl (TPTAM) radical was qualified as a pHe electron paramagnetic resonance (EPR) molecular reporter. Methods: Calibration of hyperfine splitting as a function of pH was performed using a 1.2‐GHz EPR spectrometer. Gadolinium‐diethylenetriamine pentaacetic acid (Gd‐DTPA) was used as an extracellular paramagnetic broadening agent to assess the localization of TPTAM when incubated with cells. In vivo EPR pH‐metry was performed in MDA, SiHa, and TLT tumor models and in muscle. Bicarbonate therapy was used to modulate the tumor pHe. EPR measurements were compared with microelectrode readouts. Results: The hyperfine splitting of TPTAM was strongly pH‐dependent around the pKa of the probe (pKa = 6.99). Experiments with Gd‐DTPA demonstrated that TPTAM remained in the extracellular compartment. pHe was found to be more acidic in the MDA, SiHa, and TLT tumor models compared with muscle. Treatment of animals by bicarbonate induced an increase in pHe in tumors: similar variations in pHe were found when using in vivo EPR or invasive microelectrodes measurements. Conclusion: This study demonstrates the potential usefulness of TPTAM for monitoring pHe in tumors. Magn Reson Med 77:2438–2443, 2017. © 2016 International Society for Magnetic Resonance in Medicine